The Effect Of Cooperative Learning Model Of Student Team Achievement Division (Stad) Type In Attempt To Improve Student Tolerance Character - Habsiah, Siti (International Journal Pedagogy of Social Studies, 2017)
This study was conducted to find out the influence of cooperative learning model of Student Team Achievement Division (STAD) type in attempt to improve student tolerance character in IPS learning in SMP Negeri 29 Bandung. The study is a type of quasi-experimental study using the design of Nonequivalent Control Group Design. The free variables in this study are cooperative learning model of Student Team Achievement Division (STAD) and the dependent variable is student tolerance character. The sample of study uses purposive sampling technique. The learning activities were carried out in two classes namely class VIII B as experimental class and class VIII F as control class. Study data obtained from the questionnaire that has been filled by students before and after treatment. The analysistechnique uses hypothesis test with T-Test. After processing data in experimental class usingtreatment in the form of STAD method, it is found that there is a significant improvement, while in control class using lecture method and there is no significant improvement. Based on the study that has been conducted, it can be concluded that there is effect from Student Team Achievement Division (STAD) method to the student tolerance character in IPS learning.